The The Effect of Leadership Style and Incentives on Service Advisor Performance at Honda Dealers in the Jabodetabek Area - Hardi, Mulyawan; Harsono, Deti Mulyo (Politeknik Piksi Ganesha Indonesia, 2025)
Since the Covid-19 pandemic, more manufacturers have shifted their business focus to after-sales services because the average operating margin of after-sales business globally is around 2.5 times the operating margin of new product sales. In the automotive sector, service advisors have an important role to increase revenue for after-sales services, therefore this study examines the effect of leadership style and incentives on the performance of Honda dealer service advisors in Jabodetabek. The research is quantitative with a sample size of 138 respondents using a purposive sampling method and the data was analyzed using multiple linear regression using the SPSS application. Based on the results of the t-test, incentives do not affect performance while leadership style affect performance. Simultaneously, two variables have a positive effect on performance with an effect of 51.7%.